Water Quality Research Journal - Water Quality Research Journal (IWA Publishing, 2026)
Water Quality Research Journal is a peer reviewed journal providing a forum for research on water quality in aquatic environments and ecosystems. Research into water quality is vital for understanding, protecting and ensuring the sustainability of water as a resource for a diversity of uses. From assessing surface and groundwater quality, tackling diffuse and industrial pollution, and conserving aquatic ecosystems and biodiversity, we are proud that Water Quality Research Journal publishes rigorous and interdisciplinary studies that take an integrative view on water quality and support public health, sustainable development, and ecological resilience.
FI 0.46
Q2
Keywords: Earth; Space & Environmental Sciences; Water Resource Management; Gestión de recursos hídricos; Acuerdos transformativos; Transformative agreements; Calidad del agua; Ecosistemas acuáticos